Features of Apoptosis, Induced by Temperature Reduction - Gulevsky, Aleksandr K.; Akhatova, Yuliya S.; Shchenyavsky, Ivan I. (Problems of Cryobiology and Cryomedicine, 2017)
We summarised and analysed here the findings on apoptosis contribution into the cell damages, caused by temperature deviation from the physiological norm (below 37Â°C). The participation of the caspases, causing the disintegration of anti-apoptotic Bcl-2 family proteins and proteolysis of the DNAase inhibitor, responsible for DNA fragmentation in the apoptosis, induced by a moderate cell cooling, was shown. An important role in cold adaptation mechanism belongs to the RNA-binding protein (cold-inducible RNAbinding protein, CIRP), which is capable to prevent the oxidative stress-induced apoptosis development. We reported here the data, confirming the participation of reactive oxygen species and antioxidant cell components: superoxide dismutase and human peroxiredoxin 1 in apoptosis and cold adaptation. Probl Cryobiol Cryomed 2017; 27(2): 97â€“109<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />